IOT Network Automation Implementation in Router Configuration Handling: Implementasi IOT Network Automation Pada Penanganan Konfigurasi Router - A F Limas Ptr; B H Hayadi (Jurnal MESIL (Mesin Elektro Sipil), 2022)
Network Automation or network automation in terms is the process of automating the configuration, management, testing, deployment, and operation of physical and virtual devices in a network. Thus, in this study, we will discuss the design of an IoT-based system for handling router configurations. This IoT-based router handling system uses the Python programming language which will be used as a command source on the server as a router configuration control. This system can also remotely use a smartphone so that it can be seen whether the configuration is running or system error. With this IoT-based router handling system, it will be easier for engineers to remotely and configure routers and save time in the router configuration process.